ENHANCING THE ROLE OF BUSINESS ASSOCIATIONS IN THE MECHANISMS OF GOVERNMENT-BUSINESS INTERACTION AT THE REGIONAL LEVEL - Mytnyk A.А. (Pressing Problems of Public Administration, 2017)
The paper analyzes the features of modern relations of business associations with public authoritiesin Ukraine and puts forward proposals as to enhancing the role of business associations in themechanisms of interaction between government and business at the regional level.